Design awareness - Sommer, Robert (California : Rinehart Press, 1972)
Discusses the role of persons who use buildings in the design process of new buildings, and methoids of evaluating existing designs in order to find new and better ones.
1. The new designers -- 2. Social scientists, too -- 3. Awareness -- 4. Environmental workshops -- 5. People's art -- 6. Space-time -- 7. The Volkswagen model -- 8. Who evaluates buildings and who pays the cost? -- 9. A data bank for design information -- 10. the new evaluator cookbook -- 11. Beyond productivity -- 12. The politics of design -- Index.
Includes index.
Keywords: ARCHITECTURE -- ENVIRONMENTAL ASPECTS